PENGARUH PENGALAMAN MEREK TERHADAP NIAT PEMBELIAN ULANG MELALUI MEDIASI KEPERCAYAAN PELANGGAN PADA PRODUK SEPEDA MOTOR SUZUKI DI KOTA BANDA ACEH - Maula Ridwan; Halimatussakdiah Halimatussakdiah (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This study aims to measure the influence of brand experience on repurchase intention and customer trust as mediators at Suzuki motorcycle in Banda Aceh. The sample used in this study is Suzuki motorcycle users totaling 203 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Nonprobability Sampling. Partial Least Square (PLS) was uses as a method of analysis to determine the effect of all the variables involved. Based on the result analysis, indicating that brand experience has an effect on customer trust, brand experience has an effect on repurchase intention, customer trust has an effect on repurchase intention, customer trust mediate the effect of brand experience on repurchase intention